Bath‐related headache controlled by zolmitriptan. Issue 5 (9th June 2015) - Tanaka, Ryota; Ando, Maya; Shimura, Hideki; Yamashiro, Kazuo; Hattori, Nobutaka
Abstract Bath‐related headache is a rare headache syndrome that is usually provoked by contact with water, such as during bathing and showering, and mostly affects postmenopausal, middle‐aged or elderly Asian women. The patient was a 59‐year‐old Japanese woman who had experienced repeated intense thunderclap headaches immediately after taking a shower. The trigger episodes for the headache were not only taking a shower, but also tooth brushing and wiping the body with a hot towel. Several medications, including NSAIDs or Ca‐channel blocker, were not effective for the headache; however, pretreatment with zolmitriptan before showering completely attenuated the attack of bath‐related headache. Previous literature showed that bath‐related headache is generally resistant to NSAIDs; and other treatments, such as nimodipine (a Ca2+ channel antagonist), also showed limited effects. As the present case showed the strong effects of triptans for the prevention of bath‐related headache, we discuss its pathophysiology and review the literature.